Fluorescent vic-dioxime-type ligand and its mono- and dinuclear complexes: The preparation, spectroscopy, and electrochemistry of its various complexes - ÖZKAYA, ALİ RIZA; ÖZER, METİN (ELSEVIER SCI LTD, 2008)
A new coumarin functionalized vic-dioxime, S,S-bis-[4-methylcoumarinyl]-dithioglyoxime (LH2), and its soluble mono- and dinuclear complexes [nickel(II), copper(II), cobalt(II), and uranyl(II)] have been reported. The fluorescent properties of the ligand and its complexes are due to the 7-mercapto-4-methylcoumarin fluorophore, which is conjugated with vic-dioxime that functions as the MN4 core. Fluorescence spectra of the probe showed a clear shift in excitation wavelength maxima upon metal binding indicating its potential use as ratio-metric metal indicator. The fluorescence of complexes was found to be highly sensitive to both polarity and protic character of the solvent used. Both mononuclear (LH)(2)M (M = Ni, Cu and Co) and homodinuclear (LH)(2)(UO2)(2)(OH)(2)) complexes have been obtained with the metal ligand ratios of 1:2 and 2:2, respectively. The characterizations of all newly synthesized compounds were made by elemental analysis, H-1 NMR, FT-IR, UV-vis, and mass (LSI-MS) data. The electrochemical investigation of the Ni(II), Cu(II), Co(II) and UO2(II) Complexes in comparison with the ligand involving oxime and coumarin moieties enabled us to identify metal-, oxime- and coumarin-based signals. (C) 2006 Elsevier Ltd. All rights reserved.
Keywords: vic-dioxime complexes; coumarin; fluorescence; nickel; copper; cobalt; uranyl; cyclic voltammetry; TRANSITION-METAL-COMPLEXES; TRINUCLEAR COMPLEXES; LIQUID-CRYSTALS; NI COMPLEX; (E,E)M M; NICKEL(II); MONO; COPPER(II); BEARING; OXIME